Bluegrass Land and Life : Land Character, Plants, and Animals of the Inner Bluegrass Region of Kentucky: Past, Present, and Future - Wharton, Mary E., 1912-1991; Barbour, Roger W., 1919-1993 (Book collections on Project MUSE., 1991)
"The Inner Bluegrass Region of Kentucky is unique in many respects: the character of its land, its native vegetation, and its indigenous animal life. The way of life developed by its human inhabitants over the past two hundred years is also unique. The interaction of these two forces- natural and human- is the focus for the collaboration by two of Kentucky's most distinguished scientists."--Front insert.